2020
DOI: 10.1093/ehjci/jeaa085
|View full text |Cite
|
Sign up to set email alerts
|

Exercise stress echocardiography of the pulmonary circulation and right ventricular-arterial coupling in healthy adolescents

Abstract: Aims  To explore the effects of age and sex in adolescents vs. young or middle-aged adults on pulmonary vascular function and right ventricular-arterial (RV-PA) coupling as assessed by exercise stress echocardiography. Methods and results  Forty healthy adolescents aged 12–15 years were compared with 40 young adults aged 17–22 years and 40 middle-aged adults aged 30–50 years. Sex distribution was equal in the three groups. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…Bossone et al showed that athletes have higher TRV compared with healthy control subjects both at rest and during exercise related to the higher SV and CO reached [35]. Interestingly, Forton et al, in a cohort of adolescents and adults who underwent EDE, found that pulmonary vascular distensibility coefficient α was inversely related to age at rest as well as during exercise [36]. These results confirm the age-related increase in pulmonary artery pressure (positive correlation) [37][38][39].…”
Section: Discussionmentioning
confidence: 78%
“…Bossone et al showed that athletes have higher TRV compared with healthy control subjects both at rest and during exercise related to the higher SV and CO reached [35]. Interestingly, Forton et al, in a cohort of adolescents and adults who underwent EDE, found that pulmonary vascular distensibility coefficient α was inversely related to age at rest as well as during exercise [36]. These results confirm the age-related increase in pulmonary artery pressure (positive correlation) [37][38][39].…”
Section: Discussionmentioning
confidence: 78%
“…In any individual, cardiac adaptations to exercise are influenced by several factors including training mode, intensity, duration and volume [1,3,19,[23][24][25][26]. Cardiac remodeling of the right ventricle in athletes was intensively investigated [6,10,[26][27][28][29][30][31][32] and different echocardiographic approaches were proposed to identify pathological changes [1,3,33]. However, so far, accepted reference values for athletes exist mainly for morphological echocardiographic measurements as highlighted in recent meta-analyses [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been named "cardiac fatigue" and encouraged discussions about detrimental effects of prolonged exercise sessions on RV remodeling [9,10,29]. In consequence, as shown for healthy adults during an exercise test, TAPSE/SPAP ratio decreased [27]. Hence, assessment of TAPSE/SPAP should be undertaken under similar conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Forton and colleagues observed an age‐related decrease of TAPSE/PASP and S′/PASP from adolescence to early adulthood in healthy volunteers. 53 In patients with atrial septal defect (ASD), initial TAPSE/PASP was shown to predict remaining symptoms after ASD closure, along with PVR index. 54 Additionally, TAPSE/PASP significantly improved after ASD closure in symptom‐free patients, but not in patients with residual symptoms.…”
Section: Non‐invasive Surrogates Of Right Ventricular–pulmonary Arter...mentioning
confidence: 99%
“…Echocardiography‐derived RV–PA coupling surrogates also gathered interest in the paediatric field, particularly owing to their non‐invasive nature. Forton and colleagues observed an age‐related decrease of TAPSE/PASP and S′/PASP from adolescence to early adulthood in healthy volunteers 53 . In patients with atrial septal defect (ASD), initial TAPSE/PASP was shown to predict remaining symptoms after ASD closure, along with PVR index 54 .…”
Section: Non‐invasive Surrogates Of Right Ventricular–pulmonary Arter...mentioning
confidence: 99%